CYP2A6 Effects on Subjective Reactions to Initial Smoking Attempt - Cannon, Dale S. (Oxford University Press, 2016)

(untitled) (Nicotine Tob Res)
INTRODUCTION: In very novice smokers, CYP2A6 genotypes that reduce nicotine metabolism to an intermediate rate may increase smoking risk, relative to both normal and slow rates. The present study examined the hypothesis that intermediate metabolism variants are associated with greater pleasurable effects of the initial smoking attempt than either normal or slow metabolism variants. METHODS: Participants were novice smokers ( N = 261, 65% female) of European descent. Predicted nicotine metabolic rate based on CYP2A6 diplotypes ( CYP2A6 Diplotype Predicted Rate [CDPR]) was partitioned into Normal, Intermediate, and Slow categories using a metabolism metric. Subjective reactions to the initial smoking attempt were assessed by the Pleasurable Smoking Experiences (PSE) scale, which was collected within 3 years of the initial smoking attempt. The effect of CDPR on PSE was tested using a generalized linear model in which CDPR was dummy coded and Intermediate CDPR was the reference condition. Gender was included in the model as a control for higher PSE scores by males. RESULTS: Lower PSE scores were associated with Normal CDPR, β = −0.34, P = .008, and Slow CDPR, β = −0.52, P = .001, relative to Intermediate CDPR. CONCLUSIONS: Intermediate CDPR-enhanced pleasurable effects of the initial smoking attempt relative to other CYP2A6 variants. This finding is consistent with the hypothesis that the risk effect of Intermediate CDPR on early smoking is a function of optimal pleasurable effects. IMPLICATIONS: This study supports our recent hypothesis that CYP2A6 diplotypes that encode intermediate nicotine metabolism rate are associated with enhanced pleasurable events following the initial smoking attempt, compared with diplotypes that encode either normal or slow metabolism. This hypothesis was offered to account for our unexpected previous finding of enhanced smoking risk in very novice smokers associated with intermediate metabolism rate. Our new finding encourages further investigation of time-dependent relations between CYP2A6 effects and smoking motives, and it encourages laboratory study of the mechanisms underlying the initial smoking enhancement in novice smokers associated with intermediate metabolism.